Pengaruh Motivasi terhadap Kinerja Karyawan - Septiannoor, Muhammad Lazuardi (Keizai, 2024)
Employee performance in an organization or company is influenced by various factors, one of which is work motivation. Motivation serves as the main driving force that encourages employees to perform their tasks enthusiastically and contribute optimally to the company. This study aims to analyze how work motivation affects employee performance at Hotel Midtown Xpress Sampit. The research employs a correlational method with a saturated sampling technique, where all 48 employees are included as respondents. In this study, data were analyzed using multiple linear regression to examine the relationship between work motivation and employee performance. Additionally, hypothesis testing was conducted using the t-test to determine the significance of the independent variables' influence on the dependent variable. The results indicate that work motivation has a positive and significant effect on employee performance. However, when work tenure was included as a control variable, it was found that length of service did not significantly affect performance. These findings suggest that companies should focus more on strategies to enhance employee motivation, such as providing rewards, creating a comfortable work environment, and offering personal development opportunities to optimize employee performance and productivity.